Evaluación de la metodología 5S como parte del mejoramiento continuo en la empresa Aglomerados Cotopaxi S.A. - López Paucar, Diego Fabián (2020)
The 5S methodology is a basic tool in quality management, ISO9001 type management systems, focused on reducing: waste, accidents, increasing productivity, and motivating people. The purpose of this research is to assess the effect of the implementation of this methodology on some variables of continuous improvement; it considers what was raised by various authors. This research is within a positivist approach, it followed a predominantly quantitative model, as it requires the participation of a sample of the company's staff, also, the interpretation of the results, it faces of a unique and unrepeatable reality, and it is our goal continuous improvement. It considers this modality, an experimental research design was used, a type of field study that correlates a continuous improvement tool with the performance of the coating production line staff in Aglomerados Cotopaxi company. It used the survey method, the same ones that served to collect the information; the surveys were conducted casually during the working hours to all staff. The chi-square method was used for the hypothesis test that compared the observed distribution of the data with an expected distribution of the data that allowed the results to be evaluated. The results show that the coating production plant accomplishes the 5S methodology but there is a need to carry out the proposed periodic evaluation that identifies the problems that are generated over time.